The Phytochemical Screening of Ethanolic Extract of Kopasanda (Chromolaena Odorata (L) RM King and H Rob) Leaves and Its Anti-Hyperglycaemic Activity in the Mouse Model Of Hyperglycaemia - Sofia, Vivi; Atiya, Ruzana; Fujiko, Muflihah (Scripta Medica, 2026)
Background/Aim: Hyperglycaemia is a defining feature of diabetes mellitus, a chronic metabolic disorder. Complications of diabetes mellitus may include vascular issues both macrovascular and microvascular as well as nervous system abnormalities or neuropathy. The herb “Kopasanda” (Chromolaena odorata (L)) has been shown to reduce blood glucose levels. This study aimed to investigate the antihyperglycaemic potential of ethanol-extracted Kopasanda leaves in male mice induced with oral glucose. Phytochemical screening was conducted to confirm the presence of bioactive constituents by identifying secondary metabolites.Methods: The test animals were randomly divided into five groups. Three groups were administered ethanol extract of C odorata leaves at doses of 5, 10 and 20 mg/kg body weight (bw) orally. The positive control group received glibenclamide (0.013 mg/kg bw), while the negative control group was given a 0.5 % w/v CMC solution at a dose of 2.5 mL/kg body weight orally.Results: Administration of the ethanol leaf extract at a dose of 5 mg/kg bw resulted in a significant 55.21 % reduction in blood glucose levels. A 38.24 % decrease was observed in the group receiving 10 mg/kg bw while a notable reduction was also recorded at the 20 mg/kg. These findings were statistically significant compared to the negative control (p < 0.05).Conclusion: Phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins and tannins in the ethanol extract of C odorata L leaves. The extract demonstrated notable antihyperglycaemic effects.